Development of a prototype for multi-function smart window by integrating photovoltaic blinds and ventilation system. (February 2019) - Jung, Woojin; Hong, Taehoon; Oh, Jeongyoon; Kang, Hyuna; Lee, Minhyun
Abstract: To address the energy consumption problem in the building sector, this study sought to develop a prototype of the multi-function smart window as a combination of the photovoltaic (PV) blinds and the ventilation system by considering two perspectives: (i) design of the multi-function smart window; and (ii) operation strategy for the multi-function smart window. The main findings can be summarized as follows. First, a comprehensive performance analysis of the multi-function smart window according to the application location of the ventilation system and the PV cell types was conducted to determine the optimal configuration of the multi-function smart window. Second, the hardware prototype of the multi-function smart window was implemented considering the PV cell type, PV tracker type, ventilation type, and filter. Finally, this study developed a software prototype that can monitor and control the multi-function smart window in real time based on the NI LabVIEW software program. Through the application of a novel building envelope system developed based on this study, it is expected that zero-energy buildings can be realized and buildings' indoor environmental quality can be improved. Highlights: Smart window combined with PV blinds and a ventilation system was proposed. This study focused on the design and operation strategy of the smart window. Integrated performance analysis was conducted to define the optimum configuration. Hardware prototype of the PV blinds and the ventilation system were developed. Software prototype was developed based on the real-time operation system.